A content analysis of information technology articles in Library Trends - Cabornay, Imelda D.; Faderon, Rosalie B. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2001)
This study sought to determine any trend in the field of librarianship as reflected in the articles of Library Trends. Specifically, it was undertaken to: 1) Find out the different areas in librarianship in which IT is being discussed; in which area/s is IT most/least discussed; 2) Find out at what period of time Library Trends registered the highest/lowest frequency of articles on information technology; 3) Determine the space allocations of theses articles; 4) Determine whether there is an increasing trend of IT articles in librarianship in Library Trends; and 5) Validate the recommendations in Campanano's thesis specifically on collection management. Content analysis was used on the articles of the journal Library Trends to determine the importance given towards the topic of information technology and its contribution to the field of librarianship as a whole.
Results showed that there is an increasing trend in the discussion of information technology articles, which means that these were continuously being given greater attention and importance. It further shows that the most discussed subject category in the field of librarianship is "Computerized Information Storage and Retrieval," with a total of 263 articles (19.94 percent) while the least discussed subject category was "Library Buildings" with only sixteen (16) articles (1.21 percent).It would be beneficial, based on the results, that the Institute of Library Science Library should continue its subscription to Library Trends, since this is a good source of current issues and trends in field the of librarianship in general.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Information technology -- Periodicals; Library Trends